THE FRACTURE MECHANICS FORMULAS FOR SPLIT-TENSION STRIPS - Ince, Ragip (Polish Soc Theoretical & Applied Mechanics, 2017)
The notched beams have been commonly used in concrete fracture. In this study, the splitting-strip specimens, which have some advantages - compactness and lightness - compared to beams, are analyzed for effective crack models. Using the Fourier integrals and Fourier series, a formula for the maximum tensile strength of concrete is first derived for an un-notched splitting-strip in the plane of loading. Subsequently, the linear elastic fracture mechanics formulas of the splitting-strip specimens, namely the stress intensity factor K-I, the crack mouth opening displacement CMOD, and the crack opening displacement profile COD, are determined for different load-distributed widths via the weight function.
Keywords: concrete; Fourier integrals; fracture mechanics; splitting test; weight functions